A real-life study on the implementation and effectiveness of exemestane plus everolimus per hospital type in patients with advanced breast cancer. A study of the Southeast Netherlands Advanced Breast Cancer registry. (April 2019) - Knapen, L.M.; Geurts, S.M.E.; Ibragimova, K.I.E.; Croes, S.; Vriens, B.E.P.J.; van den Berkmortel, F.W.P.J.; Dercksen, M.W.; van de Wouw, A.J.; Pepels, M.J.A.E.; de Fallois, A.O.J.; Lobbezoo, D.J.A.; de Boer, M.; et al.
Abstract: Purpose: We aimed to assess the implementation and effectiveness of exemestane plus everolimus treatment per hospital type in real-life, shortly after approval of everolimus. Methods: Advanced breast cancer patients treated with exemestane plus everolimus in 2012–2014 were included from the SONABRE registry. Progression-free survival (PFS) and a 12-week conditional PFS (post-hoc) were estimated by Kaplan-Meier method. The multivariable Cox proportional hazards model was performed by type of hospital and adjusted for patient, tumour and treatment characteristics. Results: We included 122 patients, comprising 48 patients treated in academic ( N  = 1), 56 in teaching ( N  = 4), and 18 in non-teaching ( N  = 2) hospitals. The median PFS was 6.3 months (95% Confidence Interval (CI) 4.0–8.6) overall, and 8.5 months (95% CI 7.7–9.3), 4.2 months (95% CI 2.0–6.3), and 5.5 months (95% CI 4.2–6.7) for the patients treated in academic, teaching and non-teaching hospitals, respectively. The adjusted Hazard Ratio (HR) for PFS-events was 1.5 (95% CI 1.0–2.2) and 1.0 (95% CI 0.5–1.9) respectively for patients treated at teaching and non-teaching hospitals versus the academic hospital. The adjusted HR for 12-week conditional PFS-events was not different between hospital types. In the first 12-week treatment period, treatment was discontinued due to early progression in one out of 48 patients in the academic versus nine out of 74 patients in the non-academic hospitals, confirmed by imaging in one and two patients, respectively. Conclusions: In our study, the median PFS was borderline significantly different between hospital types, possibly the result of a different assessment approach in the first 12-week treatment period. Highlights: The real-life overall median progression-free survival (PFS) was 6.3 months. The median PFS was borderline significantly different between hospital types. The assessment of progression seemed different in the first 12-week treatment period. We recommend physicians to broadly share protocols and treatment experience.